(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Development of society increases the demand of energy. Energy consumption is considered to be a good indicator of economic progress. We consume energy in many forms. Electricity is an important component of national development all over the world. Although electricity is a clean and relatively safe form of energy when it is used. But generation and distribution of electricity affects our environment. Electricity is generated at power plants by electromechanical generators. There are various types of power plants as nuclear power plants, hydroelectric power plants, coal - fired power plants, diesel - fired power plants, geothermal power plants, gas - fired power plants, solar -power plants, wind power plants, tidal power plants. We can classify the power plants in two types as renewable and non – renewable resources. Non – renewable resources of electricity generation have negative climate change effects and global warming. Emission of greenhouse gases from power plants is a matter of concern. The aim of the paper is the investigation and assessment of the negative effects of electricity generation on our environment. This paper reviews various types of power generation plants for their cost, efficiency, availability and long term and short term impacts on environment. Problems and issues in the application of the new technologies are also discussed. Advantages and disadvantages of using the renewable and non – renewable energy resources in India are also discussed. It is concluded that the application of new technologies in power plants and appropriate use of the renewable energy resources can change the scenario drastically. In this paper I have also discussed about the future prospects and challenges in this regard.